The Individual Village: Exploring Stylization Through 3D Modeling - Whoolery, Hayley (My University, 2024)
Many have heard the quote, “life imitates art.” Through my work, I aim to expound on the lesser-known pattern in which art imitates life. In my presentation, I have captured unique individual lifestyles and encompassed them into one unified piece. Using animation, I have brought to attention the idea that everyone has a creative style, showing that we are all living, breathing beings. I am not limiting a resident to the pattern of the environment that they are placed in, instead they are free to express themselves inside their homes however they like, in the context of my project. This idea is presented through computer animation and three-dimensional modeling, in which I have created an aesthetic village that shows my line of thinking. The village is made up of small, copy-and-paste houses and exterior decorations that are uniform in their looks. I have pushed the viewpoint that each house is the same; that on the outside, there are no differences. For the second part of my presentation, I have revealed the interior of a few of these houses. Each interior is vastly different from the next and contains color palettes and themes that show their uniqueness. I aimed to push the idea of individuality as much as possible, exaggerating the differences between the houses to better show the differences from person to person. I have presented the final creation as a video that walks through three of these houses.
Keywords: Model; House